Assessment of aggressive bladder cancer mutations in plasma cell-free DNA - Carrasco, Raquel; Ingelmo-Torres, Mercedes; Oriola, Josep; Roldán, Fiorella L.; Rodríguez-Carunchio, Leonardo; Herranz, Sandra; Mellado, Begoña; Alcaraz, Antonio; Izquierdo, Laura; Mengual, Lourdes (Frontiers in Oncology, 2023)
Background and aims: The spatial and temporal genetic heterogeneity of bladder cancer (BC) makes challenging to find specific drivers of metastatic disease, thus preventing to determine those BC patients at high risk of tumor progression. Our aim was to identify DNA mutations providing aggressive behavior to bladder tumors and analyze them in patients' cell-free DNA (cfDNA) during their follow-up after radical cystectomy (RC) in order to monitor tumor evolution.Methods: Six BC patients who underwent RC and presented disease progression during their followup were included. Next-generation sequencing was used to determine somatic mutations in several primary tumor and metastatic specimens from each patient. Shared DNA mutations between primary bladder tumor and metastatic sites were identified in cfDNA samples through droplet digital PCR.Results: Besides BC genetic heterogeneity, specific mutations in at least one of these genes -TERT, ATM, RB1, and FGFR3-were found in primary tumors and their metastases in all patients. These mutations were also identified in the patients' cfDNA at different follow-up time points. This is a provisional file, not the final typeset article Additionally, the dynamic changes of these mutations in cfDNA allowed us to determine tumor evolution in response to treatment.Conclusions: The analysis of BC mutations associated with poor prognosis in plasma cfDNA could be a valuable tool to monitor tumor evolution, thus improving the clinical management of BC patients.